Implementación de un sistema para obtener la energía producida por una estación fotovoltaica móvil con una estacionaria a fin de determinar la eficiencia de éstas - Aguayo Chanchicocha, Sergio Mesías (2022)
The lack of knowledge of the efficiency of energy produced between a mobile photovoltaic system and a stationary one generates a negative factor to evaluate the efficient generation of electric energy, so providing an optimal installation would improve its efficiency. To evaluate the maximum performance of a photovoltaic system, solar monitoring and tracking control systems can be implemented. This technological proposal aims to implement a system to compare the efficiency delivered by a mobile photovoltaic station with a stationary one, through the application of current and voltage analyzer devices, sensors that measure radiation, ambient temperature and temperature of the photovoltaic cells, also an energy manager that will help to visualize in real time the energy production generated during its operation will be used.